2019
DOI: 10.1242/jcs.233429
|View full text |Cite
|
Sign up to set email alerts
|

The Chlamydomonas flagellar membrane glycoprotein FMG-1B is necessary for expression of force at the flagellar surface

Abstract: In addition to bend propagation for swimming, Chlamydomonas cells use their flagella to glide along a surface. When polystyrene microspheres are added to cells, they attach to and move along the flagellar surface, thus serving as a proxy for gliding that can be used to assay for the flagellar components required for gliding motility. Gliding and microsphere movement are dependent on intraflagellar transport (IFT). Circumstantial evidence suggests that mechanical coupling of the IFT force-transducing machinery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…1 and Figure 4 -Supplementary Fig. 2) (Bloodgood et al, 2019;Kamiya et al, 2018). Of note, also FMG-1A is localized in flagella and its abundance was unaltered between WT and mutants in vegetative cells (Figure 1 -Supplementary Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1 and Figure 4 -Supplementary Fig. 2) (Bloodgood et al, 2019;Kamiya et al, 2018). Of note, also FMG-1A is localized in flagella and its abundance was unaltered between WT and mutants in vegetative cells (Figure 1 -Supplementary Fig.…”
Section: Discussionmentioning
confidence: 91%
“…A recent knock down study showed, that it is the main constituent of the glycocalyx surrounding the flagellum. Additionally, a fmg-1B mutant showed a drastically reduced ability to glide (Bloodgood et al, 2019). Strikingly, FMG-1B is present at a high copy number and turns over rapidly within approximately 1 h (Bloodgood, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated cytosolic Ca 2+ triggers a conformational change in Miro, which possesses two Ca 2+ -binding EF-hands, leading to the dissociation of the mitochondrion from the microtubule motor complex 43 . 37 . This allows an adherent flagellum to slide along a surface whilst maintaining contact with it.…”
Section: Discussionmentioning
confidence: 99%
“…This was first described by Ulehla (1911) and later “rediscovered” by Lewin (1952) and Bloodgood (1981). Over time, a number of studies implicated the FMG‐1B flagellar membrane glycoprotein as the key component that mechanically connected force generating machinery inside the flagellum to the flagellar surface allowing traction forces to be exerted on a solid substrate (Bloodgood, 2009; Bloodgood, Tetreault, & Sloboda, 2019). Although it was assumed that a minus‐end directed microtubule‐associated motor protein must be involved in gliding motility, identification of the exact mechanism underlying gliding motility in Chlamydomonas remained elusive until a landmark study by Shih et al (2013) showed definitively that intraflagellar transport (IFT), which had been discovered in Chlamydomonas (Kozminski, Johnson, Forscher, & Rosenbaum, 1993), is the force transduction machinery behind whole cell gliding motility as well as bidirectional, saltatory movement of polystyrene microspheres along the flagellar surface.…”
Section: The Concept Of Cell Surface Motilitymentioning
confidence: 99%